Bibliometric review of the scientific publications related to agricultural finance in South Asia - Nafeel, Mohamed Mahboob; Khamis, Munir Soud; Mansor, Fadillah (Journal of Islamic, Social, Economics and Development, 2025)
This paper examines agricultural finance research publications indexed in the Scopus database up to 2023, covering countries representing the Indian subcontinent. The paper uses specific keywords related to agricultural finance and the names of countries representing the Indian subcontinent to identify the publications and employs bibliometric analysis. Tools such as Microsoft Excel for frequency analysis, VOSviewer and Biblioshiny for data visualization and Harzing's Publish or Perish for citation metrics and analysis were used. Scopus yielded 46 research publications on agricultural finance in South Asia from 1979 to 2023, suggesting a slow but consistent growth in scientific publications on agricultural finance in each decade, with India being the leading contributor. The Agricultural Finance Review recorded the most articles and citations related to the research domain. The results suggest a shift in the research clusters towards productivity and growth aspects, socioeconomic factors, and risk management function of agricultural finance including climate change adaptation. The study presents the findings of a bibliometric analysis, focusing on standard indicators such as publication growth, dominant research clusters in the selected region, collaboration, productive authors and countries, top institutions, primary journals, and high impact articles.